Taṭwīru Mādah al-Lughah al-‘Arabiyyah ‘ala Asāsi al-Ta‘allum al-Ta‘āwuni - Ady Muh. Zainul Mustofa (Alsina : Journal of Arabic Studies, 2020)
Learning Arabic in MTs Unggulan Hikmatul Amanah in Amanatul Ummah Islamic Boarding School really noticed a reading skill in the learning process, so that the students would be able to read Islamic religion literature written in Arabic language. This study aimed to describe developing process of Arabic language teaching material with Cooperative Learning approach for 7th grade students MTs Unggulan Hikmatul Amanah and to know a validity and also an effectiveness of the teaching material. Type of this study used developing steps by Borg and Gall in Sugiono’s book. Data in this study, had qualitative and quantitative. It was collected with interviews, questionnaire and tests.  Meanwhile, the data was analyzed descriptively and T test.  The results of this study indicate that the teaching materials developed are appropriate and effective for teaching Arabic at this level after going through a process of improvement based on expert judgment and field trials.